HUBUNGAN TERPAAN ISU HOAKS VAKSINASI COVID-19 TENTANG EFEK SAMPING SETELAH VAKSINASI DAN PERSEPSI MASYARAKAT TENTANG PROGRAM VAKSINASI COVID-19 DENGAN MINAT MELAKUKAN VAKSINASI COVID-19 PADA MASYARAKAT KOTA BONTANG - Aldy Rizaldy Ramadhan; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
This research aims to describe the public’s acceptance of exposure to issues about side effects after vaccination, the public perception of the COVID-19 vaccination program, and the community action around the COVID-19 vaccination program. The study was using the theory of individual differences and the risk perception attitude framework with positivistic paradigm using the Kendall’s Tau B analysis. The object of the research was the citizen of Bontang who were exposed to the COVID-19 vaccination hoax, with a research sample of 51 respondent. The results of the study showed that the significance value for the COVID-19 vaccination hoax issues exposure about side effects after vaccination was 0,673, which means that the two variables showed no relations. While the results of people’s perception of the COVID-19 vaccination program showed a significance value of 0,015, which means that the two variables have a positive relationship. The second theory, Risk Perception Attitude Framework, is proven in this study. The findings of this study shows that the majority of respondents are in the responsive group and the proactive group. However, there is a small percetage of respondents who are in the anxious group and the indifferent group this has a negative impact on the COVID-19 pandemic and vaccination program.